An Empirical Investigation of the Structure-Conduct-Performance Paradigm in the General Insurance Market - Tsang, Thomas (2011)
This research aims to provide evidence on the SCP paradigm using recent accounting data. The study looks at the insurance market, specifically the general insurance market using an industrial organisations approach. Previous literature has provided mixed evidence on SCP. Further evidence is required because of the implications on the efficacy of competition policy.